ILLEGAL, UNREPORTED AND UNREGULATED FISHING: THE IMPACTS AND POLICY FOR ITS COMPLETION IN COASTAL WEST OF SUMATERA - Nova, Sri Asih Roza (Indonesian Journal of International Law, 2017)
For coastal States, IUU fishing is a classic problem. This issue has become a thorn in the flesh, despite being attempted various ways to overcome them, but until now it still has been resolved yet. IUU fishing action can cause many problems, such as increasing poverty of coastal communities, making bankruptcy of fisheries industry, damaging ecosystems and fish habitat in the ocean, disrupting stability of security coastal countries, damaging of diplomatic relations between the coastal States and so on. To that end, this article tries to analyze more deeply about IUU fishing and it’ problems in Indonesia